균형성과표를 활용한 건설사업관리의 핵심성과지표 도출 - 임우석; 정지현; 이학기; Lim, Wooseok; Jung, Jihyun; Lee, Hakki (한국건설관리학회 논문집, 16(6), 2015)
Enterprises should set up realizable goals and continually control the goals from apprehending whether they can be realized or not so that the enterprises grow consistently. Furthermore, from supplementing parts to be improved, goals are reset and the result should be controlled in order to fit to them. Lately, a lot of discussions about the results of organizations, projects, and companies are being realized in construction field. Particularly, in construction management, effective and professional control activities throughout the life cycle of facilities as well as the stage of business implementation of construction work are needed. About the result measurement of the construction management, lots of most domestic researches stay in the level of establishing basic concepts. Also, since characteristics of the construction field and the construction management were not reflected properly, it is in a situation that the result control system is not applied to on-site real works. Hence, this study intends to suggest fundamental data for measuring objective results from extracting result areas and key performance indicators of the construction management using Balanced Score Card. 기업이 지속적으로 성장하기 위해서는 실현가능한 목표를 설정하고 그 목표를 달성하였는지 파악하여 끊임없이 목표를 관리하여야 한다. 나아가 개선해야 할 부분을 보완하여 목표를 재설정하고 그에 맞도록 성과를 관리하여야 한다. 최근 건설 분야에서도 조직, 프로젝트 및 기업의 성과에 대해서 많은 논의가 이루어지고 있다. 특히 건설사업관리는 건설공사의 사업수행 단계는 물론 시설물 생애주기에 걸쳐 효율적이고 전문적인 관리활동이 요구된다. 건설사업관리의 성과측정에 대해 국내의 많은 연구 대부분은 성과측정 모델의 기본적인 개념을 정립하는 수준에 머물러 있다. 또한, 건설현장 및 건설사업관리의 특성이 제대로 반영되지 못하여 성과관리시스템을 현장 실무에 적용하지 못하고 있는 실정이다. 따라서 본 연구에서는 균형성과표를 활용한 건설사업관리의 성과영역 및 핵심성과지표를 도출하여 객관적인 성과측정을 위한 기초자료를 제시하고자 한다.